A case of ramucirumab-related gastrointestinal perforation in gastric cancer with small bowel metastasis - Shinya Urakawa; Daisuke Sakai; Yasuhiro Miyazaki; Toshihiro Kudo; Aya Katou; Chiaki Inagaki; Koji Tanaka; Tomoki Makino; Tsuyoshi Takahashi; Yukinori Kurokawa; Makoto Yamasaki; Kiyokazu Nakajima; et al. (Surgical Case Reports)
Abstract Background Ramucirumab is a monoclonal antibody targeting vascular endothelial growth factor receptor 2 (VEGFR-2). Ramucirumab either alone or in combination with paclitaxel (PTX) has been found to be safe and effective for patients with previously treated advanced gastric cancer. One of the serious adverse events associated with ramucirumab is gastrointestinal (GI) perforation. Case presentation We report the case of a 67-year-old man who developed a ramucirumab-related GI perforation while undergoing treatment for gastric cancer with small bowel metastasis. He underwent laparoscopic total gastrectomy following neoadjuvant chemotherapy in January 2015 and was diagnosed with hepatic and bone recurrence in October 2015. Ramucirumab in combination with PTX was administered for one and half months after first-line chemotherapy failure. He presented with abdominal pain 7 days after the last ramucirumab dose, and emergency exploratory surgery revealed a small intestinal perforation. Pathological findings indicated that it occurred in a zone containing a small intestinal tumor, which was found to be metastasis of the gastric cancer. He had no postoperative complications, but chemotherapy was not reintroduced and he died 3 months later. Conclusion We present a recent case of ramucirumab-related gastrointestinal perforation in gastric cancer with small bowel metastasis. This case is rare, but important to consider.